Zu Jer 33,11 - Herrmann, Wolfram (Biblische Notizen, 2004)
The Greek version of the Septuagint as well as Theodotion render the noun הודה in Jer 33,11 by the plural of Srapov, the Latin Vulgate, following this usage, by the plural of votum. Exegetically here a problem remained. The present author wants to confront the reader with a solution of it. In the face of the spreading spiritual apprehension of the sacrifice in course of time the Greek translation probably aimed at counteracting thereto, because the hope was alive the sacrificial cult would again be possible.